Management of TMD in patient with canted occlusal and asymmetry - Fitrya Dyah Wijayanti; Ira Tanti (Indonesia Prosthodontic Association, 2024)
Facial asymmetry can disturb not only appearance but also function. The most characteristic of the TMJ internal derangement (ID) is the disc displacement in patient with face asymmetry. To report the successful treatment of TMJ ID in class 2 malocclusion with canted occlusal plane and facial asymmetry. A 22-year-old male patient came refer by the Orthodontics Department with chief complaints of slanted jaw and bite, soreness, tension in front of right ear region. History of closed lock on his right jaw and had clicking on his left. He’s a daytime bruxer. Clinical examination showed visible canting in the occlusal plane, reciprocal clicking in the left TMJ, limited movement and deviation when opening and closing the mouth. Based on panoramic x-ray, the left mandibular ramus was longer than the right. The DC-TMD diagnosis is disc displacement with reduction on the left and disc displacement without reduction without limited opening on the right TMJ. A stabilization appliance (SA) was fabricated for him. Patient was instructed to do jaw exercise, and physical-self regulation (PSR). Patient was also told that emotional stress, and bad habit should be reduced. After 4 months using the SA, and doing the jaw exercise and PSR, the patient showed significant improvement. Soreness and tension had disappeared, and facial asymmetry was getting better. Patient then was referring to Orthodontic Department to treat his malocclusion. SA, jaw exercise and PSR were a good treatment choice to manage the TMJ ID. Keywords: facial asymmetry, TMJ internal derangement, disc displacement